Sofosbuvir terminated RNA is more resistant to SARS‐CoV‐2 proofreader than RNA terminated by Remdesivir (2020)
SARS-CoV-2 is responsible for COVID-19, resulting in the largest pandemic in over a hundred years. After examining the molecular structures and activities of hepatitis C viral inhibitors and comparing hepatitis C virus and coronavirus replication, we previously postulated that the FDA-approved hepatitis C drug EPCLUSA (Sofosbuvir/Velpatasvir) might inhibit SARS-CoV-2.We subsequently demonstrated that Sofosbuvir triphosphate is incorporated by the relatively low fdelity SARS-CoV and SARS-CoV-2 RNA-dependent RNA polymerases (RdRps), serving as an immediate polymerase reaction terminator, but not by a host-like high fdelity DNA polymerase. Other investigators have since demonstrated the ability of Sofosbuvir to inhibit SARS-CoV-2 replication in lung and brain cells; additionally, COVID-19 clinical trials with EPCLUSA and with Sofosbuvir plus Daclatasvir have been initiated in several countries. SARS-CoV-2 has an exonuclease-based proofreader to maintain the viral genome integrity.Any efective antiviral targeting the SARS-CoV-2 RdRp must display a certain level of resistance to this proofreading activity.We report here that Sofosbuvir terminated RNA resists removal by the exonuclease to a substantially higher extent than RNA terminated by Remdesivir, another drug being used as a COVID-19 therapeutic.These results ofer a molecular basis supporting the current use of Sofosbuvir in combination with other drugs in COVID-19 clinical trials.